Interleukin-25 Produced by Synoviocytes Has Anti-inflammatory Effects by Acting As a Receptor Antagonist for Interleukin-17A Function - Lavocat, Fabien; Ndongo-Thiam, Ndiémé; Miossec, Pierre (Frontiers in Immunology, 2017)
The production and function of cytokines are highly regulated. One mechanism is the balance between pro- and anti-inflammatory cytokines. As IL-17A and IL-25 share the IL-17RA receptor chain, we hypothesize that IL-25 acts as an IL-17A receptor antagonist and limits its pro-inflammatory effects. The production and expression kinetics of IL-25 and its receptor chains IL-17RA and RB were analyzed in rheumatoid synoviocytes alone or in co-culture with PBMCs. The effects of autocrine or exogenous IL-25 on synoviocytes were investigated in the presence or not of an anti-IL-25 antibody. To study the regulatory effects of IL-25, synoviocytes and/or PBMCs were exposed to IL-25 before being treated with IL-17A and TNF-α alone or combined. IL-25, IL-6 and bioactive IL-17A were quantified in RA patient plasma. Synoviocytes expressed and secreted IL-25, and expressed the two chains of its receptor IL-17RA and IL-17RB. IL-17RB expression was increased by TNF-α. IL-25 production occurred at a delayed time point (5 days) after stimulation with IL-17A and TNF-α. Synoviocytes pre-treated with IL-25 were less responsive to IL-17A and TNF-α. PBMCs exposed to IL-25 showed a decreased production of pro-inflammatory mediators, including IL-17A with a 57% decrease; p=0.002. IL-25 levels were elevated in the plasma of RA patients compared to healthy subjects (p=0.03). However, these levels are not high enough to inhibit the function of circulating IL-17A. In conclusion, it was shown for the first time that synoviocytes produce IL-25, specifically at late time-points and that IL-25 acts as a regulator of IL-17A-driven inflammation, as indicated by in vitro results and in vivo, in a long-term RA patient follow-up. These results may be important when considering IL-17A inhibition.